دور النقل البحري في التأثير على فعالية سلاسل الإمداد دراسة حالة دولة الإمارات العربية المتحدة - زياد،غيلاني; أيمن، حليلات; نذير،بالي; سليمة،محلو (university of eloued جامعة الوادي, 2024)
أظهرت الدراسة أن للنقل البحري تأثيرًا كبيرًا على فعالية سلاسل الإمداد، وتشمل هذه التأثيرات الربط العالمي والذي بدوره يوفر النقل البحري وسيلة فعالة لربط مختلف البلدان والمناطق، مما يسهل حركة البضائع والسلع بينها، والقدرة على نقل كميات كبيرة بحيث تتميز سفن النقل البحري بقدرتها على نقل كميات هائلة من البضائع في رحلة واحدة، مما يجعلها خيارًا اقتصاديًا لعمليات النقل لمسافات طويلة، وخاصة التكلفة المنخفضة والتي يُعد النقل البحري فيها أحد أكثر وسائل النقل تكلفة، مما يساهم في خفض تكلفة المنتجات النهائية للمستهلكين وأخيرا المرونة والتي بدورها توفر للنقل البحري مرونة كبيرة في اختيار مسارات الشحن وتوقيتها. و تُساعد الخدمات اللوجستية في تخطيط سلاسل الإمداد من خلال تحديد احتياجات النقل والتخزين والتوزيع، كما تُنفذ الخدمات اللوجستية الأنشطة الفعلية لنقل البضائع وتخزينها وتوزيعها، ويشهد قطاع النقل البحري في دولة الامارات العربية المتحدة نموا مطردا من حيث الموانئ، وتشغيل السفن، وبناء وصيانة أحواض السفن، وفقا للمعايير الدولية بشأن السلامة البحرية وحماية البيئة البحرية. The study showed that maritime transport has a significant impact on the effectiveness of supply chains. These effects include global connectivity, which in turn provides maritime transport as an effective means of connecting various countries and regions, facilitating the movement of goods and commodities between them, and the ability to transport large quantities, so that maritime transport ships are distinguished by their ability to transport large quantities. Huge amounts of goods in one trip, making it an economical option for long-distance transportation operations, especially the low cost in which sea transportation is one of the most expensive means of transportation, which contributes to reducing the cost of final products to consumers and finally flexibility, which in turn provides sea transportation with great flexibility in choosing routes. Shipping and timing. Logistics services help plan supply chains by identifying transportation, storage, and distribution needs. Logistics services also carry out the actual activities of transporting, storing, and distributing goods, The maritime transport sector in the United Arab Emirates is witnessing steady growth in terms of ports, ship operation, and the construction and maintenance of shipyards, in accordance with international standards regarding maritime safety and protection of the marine environment.
مذكرة ماستر علوم تجارية
Keywords: النقل البحري; سلاسل الإمداد; الخدمات اللوجستية maritime transport; supply chains; logistics services